Investigation of heavy metal distributions along 15m soil profiles using EDXRF, XRD, SEM-EDX, and ICP-MS techniques - Akbulut Özen, Songül; Ozkalayci, Fatih; Cevik, Ugur; Van Grieken, Rene (Wiley, 2018)
The research of soil contamination by heavy metal is an important field due to its environmental and health implications. The goal was to study the elemental mobility as a function of depth. For this reason, the distribution of heavy metals (V, Cr, Co, Ni, Cu, Zn, As, Sn, and Pb) was investigated along soil profiles up to a depth of 15m at 9 sampling sites in the Nilufer industrial district (Bursa, Turkey). Elemental analyses were done with the Epsilon 5 energy dispersive X-ray fluorescence and inductively coupled plasma mass spectrometry equipment. Particle analysis was performed with a JEOL scanning electron microscope equipped with a Si(Li) X-ray detector. The crystallographic compositions of oxide compounds in soil samples were identified by a Rigaku X-ray diffraction instrument. Different parameters such as the soil's chemical (mineralogical structure, pH, and electrical conductivity) and physical properties (the number of blows, the stiffness index, the liquidity index, the plasticity index, and the water content) were analyzed. To assess the mobility of the heavy metals, diffusion (D) and convection coefficients (?) were calculated with the finite difference method. Convection was determined to dominate the studied region. In addition, the mobility coefficient was determined for each metal. High mobilities were determined for Zn and V, moderate mobilities for Cr, Ni, Cu, and As, and low mobilities were determined for Co and Pb. The results revealed that elements had reached depths of up to 15m, causing irreversible soil contamination that may lead to environmental health issues.
Keywords: [No Keywords]